PERSPECTIVE OF RELEVANCE OF ANCIENT KANNADA LITERATURE SOCIAL SITUATION - B. S. Ganganalli (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Literature is the history of man. It is necessary for another man to understand the history of man at any time. It is also the culture of man. Literature shows the cultural history of man as history reveals the culture of a nation. We can find the source of the research that has been done to consider the Ramayana and Mahabharata as ancient history in this context. It is in this sense that Pampa said, ’Manushya jati taanonde valam’. Therefore, ancient literature is relevant to us even today. The longer we try to search and understand literature from the past, the more we will be able to understand the basic values ​​of man’s ancient culture from that time. The way man lived. The nature of the culture of his country. Politics, legislation, social situation. His unspoken experiences are filled in the pages of ancient works. For example: ‘Kaveriyndama Godavarivaramirda nadada Kannadadol palattida janapadam vasudhavalaya vilena vishad vidhi vishaham’ This line of the poet reveals the knowledge of the geography (area) of ancient Karnataka and the specialty of the folklore. In it, ‘Puligerey okkunda naduvana nade Kannada Tirul’ is the word that is spoken by the poets. The poets are truly knowledgeable about poetry, experienced in the art of poetry’ and ‘Subhatarkal poets are great masters, great men